إدارة برنامج تكلم بالعربية لتحسين كفاءة المعلمين في المدرسة المتوسطة الإسلامية سبيل الله مالانج - Fitria, Fitria; La Udin, Yadin; Kholid, Nur; Arifa, Zakiyah (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
This research aims to analyze the school of Sabilallah Malang in improving the competence of the Arabic language teacher. This research used a qualitative approach to gain in-depth knowledge about the phenomenon. The research conducted a case study, a type of descriptive analytical research. To collect data, this research used three methods: interview, direct observation, and document analysis. To analyze the data, this research follows the principles and benefits of the management process developed by George R. Terry, namely planning, organizing, actuating, and evaluation. This analysis aims to reach knowledge and understanding about the activities carried out by the school in upgrading the competence of the Arabic language teacher. The results of this research are that in the Islamic Junior High School Sabilillah Malang there is a program to improve the competence of Arabic language teachers. The Speak Arabic program consists of an activity, including teaching Arabic especially to teachers, accustoming the daily phrase, and learning Arabic for Arabic language teachers.